Manajemen Masjid Al-Aqobah 7 Palembang dalam Meningkatkan Kesejahteraan Jamaah - Ela Puspita; Nurseri Hasnah Nasution; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Mosques do not only function as places of worship but also play a strategic role as centers for community empowerment and welfare improvement. The success of this role is highly influenced by the management practices implemented by mosque administrators. This study aims to analyze the management of Al-Aqobah 7 Mosque in Palembang in improving the welfare of its congregation. This research employs a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation. The research informants consisted of mosque administrators, volunteers, and congregation members involved in various mosque programs. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that Al-Aqobah 7 Mosque has implemented management functions consisting of planning, organizing, actuating, and controlling in carrying out congregation service programs. The implementation of these management functions is reflected in innovative programs such as free vehicle washing services and the Sunday Morning Vegetable Charity Program. These programs not only serve as social service activities but also function as strategies to increase congregation participation in mosque activities. The success of the programs is supported by collaboration among administrators, volunteers, and community members. The programs have positively impacted the congregation’s welfare in social, economic, and psychological aspects. This study concludes that well-planned and service-oriented management can transform a mosque into a center of community empowerment and sustainably improve the welfare of its congregation.